Accelerated pace of frailty in patients with schizophrenia - Shun Yao; Lijun Wang; Zhiying Yang; Yichong Xu; Xiaoqing Zhang; Yuan Shi; Donghong Cui (Elsevier, 2025)
Background: Schizophrenia is associated with an increased risk of mortality and physical comorbidities, indicating a potentially accelerated frailty process in affected individuals. This study aimed to test association between schizophrenia and frailty using the frailty index based on laboratory markers (FI-Lab). Methods: A total of 600 patients with schizophrenia and 518 healthy controls, aged between 20 and 69 years were included in the present study. Frailty was assessed using the FI-Lab, incorporating routine laboratory markers, body mass index, and blood pressure measurements. FI-Lab for patients with schizophrenia and healthy controls was compared, with stratification by age group and sex. In addition, robust was defined as FI-Lab ≤ 0.12, pre-frail as 0.12-0.25, and frail as >0.25. Multiple linear regression analysis was used to test the association between schizophrenia and FI-Lab. Multinomial logistic regression was used to test the association between schizophrenia and frailty status. Spearman correlation analysis was performed to assess the relationship between the Positive and Negative Syndrome Scale (PANSS) scores and FI-Lab in schizophrenia patients. Results: Schizophrenia patients exhibited significantly higher FI-Lab than healthy controls across all age groups, indicating accelerated pace of frailty in schizophrenia patients. Schizophrenia was significantly associated with FI-Lab (β = 0.044, p = 0.004) in the adjusted model. Schizophrenia was significantly associated with both pre-frail status (OR = 2.26, 95% CI = 1.40−3.68, p = 0.001) and frail status (OR = 10.33, 95% CI = 5.65−19.93, p = 0.007) compared to robust status in the adjusted model. Additionally, a positive correlation between FI-Lab and PANSS scores suggests that more severe schizophrenia symptoms correlate with higher degree of frailty. Conclusion: These findings suggest that schizophrenia contributes to an increased risk of frailty. The FI-Lab provides a quantitative measure of frailty. This underscores the importance of integrating frailty considerations into the treatment and management of schizophrenia.